PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF TERHADAP HASIL BELAJAR SISWA DI SEKOLAH DASAR - Annisa Fitri Auliya,; Eneng Fitriasari,; Mutia Nurunnisa,; Arita Marini, (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
This study aims to determine the effect of using interactive learning media on student learning outcomes in elementary schools and to determine student learning achievement. The method used is library research and data collection is done by tracing several journals, articles, books accessed through online. The use of interactive learning media can make it easier for students to understand the subject matter, because the media display is very attractive so that students play an active role in the learning process. The results of this study indicate that the use of interactive learning media in elementary schools has a significant effect on student learning outcomes.